Beyond sun and sand : Caribbean environmentalisms - Baver, Sherrie L.; Lynch, Barbara D. (Rutgers University Press, 2006)
Filtered through the lens of the North American and European media, the Caribbean appears to be a series of idyllic landscapes-sanctuaries designed for sailing, diving, and basking in the sun on endless white sandy beaches. Conservation literature paints a similarly enticing portrait, describing the region as a habitat for endangered coral reefs and their denizens, parrots, butterflies, turtles, snails, and a myriad of plant species. In both versions, the image of the exotic landscape overshadows the rich island cultures that are both linguistically and politically diverse, but tr.